HUBUNGAN ASUPAN ZAT GIZI DENGAN KOMPOSISI TUBUH REMAJA - Lisnawati, Naintina; Haryanto, Irwan (Journal of Holistic and Health Sciences (Jurnal Ilmu Holistik dan Kesehatan), 2018)
Background: Adolescence is characterized by changes in body composition caused by hormonal conditions and lifestyle. These conditions have an influence on the pattern of food intake consumed by adolescents. Objective: To describe and analyze the correlation of nutritional intake and body composition of adolescents. Method: This study used cross sectional design. Subjects of the study were adolescents in Purwakarta Regency which selected randomly amounted to 44 people. Nutritional intake data used Food Recall Form 2x24 hours and body composition measurement used Bio Impedance Analysis (BIA). Data analysis used Rank Spearman Test. Results: Mean of subjects’s body weight and lean body mass (LBM) were 43.7±8.6 kg, 33.8±5.2 kg, respectively. Most of level of energy intake of subjects were less (59.1±37.8%), so did calcium (159.4±502.9 mg). Intake of energy, carbohydrate, protein, and fat correlated with body composition of subjects (p<0.05), while intake of iron (Fe), calcium (Ca), Potassium (K), Sodium (Na), Magnesium (Mg), and Zinc (Zn) not sigificantly correlated with body composition of subjects (p>0.05). Zn was being the only micronutrient which correlated to fat mass (p=0.032). Conclusion: Macronutrients have significantly correlated with body composition among adolescents in Purwakarta Regency.